Study of knowledge in diarrhea and personal hygiene among students below 10 years old in SD Santo Yoseph 2, Denpasar in 2016-2017 - Karthigeyan Manogaran; I Made Gede Dwi Lingga Utama; I Wayan Gustawan (Intisari Sains Medis, 2019)
Background: The lack of basic knowledge of diarrhea and also poor self-hygiene might be the risk factors of diarrhea.Aim: The study aims to identify the knowledge of diarrhea and personal hygiene among student below 10 years old in SD Santo Yoseph 2, Denpasar, Bali. Method: This cross sectional study was conducted on students below 10 years old in SD Santo Yoseph 2, Denpasar. Fifty students participated in this study, and they were divided into two groups. Of total study participants, 25 were from 8 years old, and 25 were from 9 years old. They were asked to fill up a self-administered questionnaire. The variables assessed were their knowledge of diarrhea (definition, etiology, risk factors, sign and symptoms, complications, treatment and management, and prevention) and application of personal hygiene.Result: About 34% of 50 students below 10 years old in SD Santo Yoseph respectively had good knowledge of diarrhea. However, 66% of students had very less knowledge about diarrhea where they get below. For the application of personal hygiene, 24% of students managed to get a good score while 74% of them failed to get a good score. The vast majority had adequate knowledge of the definition of diarrhea. At the same time, the majority of the students was unable to know that dehydration is the complication of diarrhea due to the loss of a large amount of water and salt in the body.Conclusion: Though the overall knowledge in diarrhea and application of hygienic lifestyle among the students were poor, few minorities of the students had a good understanding of both these variables. There is a strong need for early childhood education about knowledge in diarrhea and personal hygiene in school level itself as a method of prevention.